CHALLENGES AND STRATEGIES IN IMPLEMENTING MULTICULTURAL EDUCATION IN SOCIOECONOMICALLY DIVERSE ELEMENTARY CLASSROOMS - Hasanah; Maksum, Arifin; Nurhasanah, Nina (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: The growing economic diversity in elementary schools presents significant challenges to the effective implementation of multicultural education. Students from different socioeconomic backgrounds often experience varied levels of access to resources and support, which influences their engagement and outcomes in multicultural learning environments. Purpose: This study aims to investigate the obstacles and potential strategies for implementing multicultural education in socioeconomically diverse elementary classrooms, focusing on how economic diversity impacts student engagement, teacher preparedness, and parental expectations. Novelty: While previous research has explored racial and ethnic diversity in education, this study uniquely addresses the underexplored dimension of socioeconomic diversity, adding depth to multicultural education frameworks by emphasizing economic inclusivity. Research Methods: A qualitative approach was utilized, involving semi-structured interviews with teachers, administrators, and parents, along with classroom observations in economically diverse elementary schools. Thematic analysis was conducted to identify key patterns and challenges. Results: The study reveals that economic diversity can hinder multicultural education effectiveness due to resource disparities, inconsistent teacher training, and varied parental expectations. Schools with higher funding reported better engagement and outcomes, highlighting the importance of resource allocation. Research Contributions: This research provides theoretical insights by integrating economic diversity into multicultural education frameworks and practical recommendations for educators and policymakers to enhance inclusivity in diverse school settings.